Titik temu pemikiran pendidikan Ki Hajar Dewantara dengan pemikiran tokoh pendidikan Islam di Indonesia - Syafri, Ulil Amri; Frandani, Muhammad; Suryati, Suryati; Wasto, Wasto; Tamam, Abas Mansur (Tawazun: Jurnal Pendidikan Islam, 2023)
The history of Islamic education civilization in Indonesia began from the history of Islamic education in the world. The scholars are the great bridge for spreading knowledge, which is the essence of Islamic educational civilization. The acculturation of Islamic culture and civilization brought by Arab and Persian traders has shaped Indonesia into a religious nation with a strong cultural pattern. Hadaratussyaikh Kiai Haji Muhammad Hasyim Asy'ari (1871-1947), Shaykh Abdullah Ahmad (1878-1933), Muhammd Natsir (1908-1993), A. Hasan (1889-1959). And Ki Hajar Dewantara (1889-1959) is a line of figures who shaped and colored the civilization of Islamic education in Indonesia. Through these figures, we find Indonesian educational civilization, rich in religious and cultural meanings, united in a balanced concept. This research is qualitative research with a literature review. In order to obtain representative data in the discussion of this paper, the library research method is used by searching, collecting, reading, and analyzing books that are relevant to the research problem. The study results show a relation between the thoughts of Islamic education civilization figures and the Maestro of National education and culture. Such as; The aims of edsucation are human salvation and happiness, the urgency of religion in the educational process, education accepting change in response to globalization, and education is the responsibility of every human being. Abstrak Sejarah peradaban pendidikan Islam di Indonesia berakar dari sejarah pendidikan Islam di dunia. Adalah para ulama jembatan besar bagi tersebarnya keilmuan yang merupakan inti sari peradaban pendidikan Islam. Akulturasi budaya dan peradaban Islam yang dibawa oleh pedagang Arab dan Persia membentuk Indonesia menjadi bangsa yang agamis dengan corak budaya yang kental. Hadratussyaikh Kiai Haji Muhammad Hasyim Asy'ari (1871 - 1947), Syaikh Abdullah Ahmad (1878-1933), Muhammd Natsir ( 1908-1993), A. Hassan ( 1889-1959). Dan Ki Hajar Dewantara (1889-1959) merupakan jajaran tokoh yang membentuk dan mewarnai peradaban pendidikan Islam di Indonesia. Lewat tokoh-tokoh tersebutlah kita mendapati peradaban pendidikan Indonesia yang begitu kaya akan makna religius dan budaya yang menyatu dalam balutan konsep yang seimbang. Penelitian ini bersifat kualitatif dengan menggunakan metode studi tokoh, yaitu suatu pengkajian sistematis terhadap pemikiran atau gagasan seorang pemikir muslim, baik sebagian maupun keseluruhannya. Hasil penelitian menunjukkan bahwa ada titik temu antara pemikiran tokoh peradaban pendidikan Islam dengan Maestro pendidikan dan kebudayaan Nasional, yaitu Pendidikan ditujukan ke arah keselamatan dan kebahagiaan manusia, urgensi agama dalam proses pendidikan, pendidikan menerima perubahan demi menjawab perubahan zaman, dan pendidikan adalah tanggung jawab setiap manusia.